Growing up tobacco free : preventing nicotine addiction in children and youths - Lynch, Barbara S.; Bonnie, Richard J. (National Academy Press, 1994)
A report from the Committee on Preventing Nicotine Addiction in Children and Youths, Division of Behavioral Sciences and Mental Disorders, the Institute of Medicine.
Keywords: Children -- Tobacco use -- United States -- Prevention.; Youth -- Tobacco use -- United States -- Prevention.; Children.; Infants.; Smoking Prevention; Adolescent; Child; Infant; Smoking; Tobacco Use Disorder; Tobacco Use Disorder -- prevention & control; United States; Enfants -- Tabagisme -- États-Unis -- Prévention.; Jeunesse -- Tabagisme -- États-Unis -- Prévention.; Enfants.; Nourrissons.; Tabagisme.; Enfance.; children (people by age group); infants.; childhood.; SELF-HELP -- Substance Abuse & Addictions -- General.; PSYCHOLOGY -- Psychopathology -- Addiction.; Infants; Children; Children -- Tobacco use -- Prevention; Youth -- Tobacco use -- Prevention; Tabagisme -- Prévention.; Jeunesse -- Usage du tabac -- Prévention.; Government publications